How Effective Have Poverty and Social Impact Analyses Been? - World Bank (Washington, DC, 2012)
The Poverty and Social Impact Analysis (PSIA) approach, introduced by the World Bank in FY02, aimed to help the Bank and its client countries anticipate and address the possible consequences of proposed policy reforms, especially on the poor and vulnerable, and to contribute to country capacity for policy analysis. According to the Bank, by FY07 it had undertaken 156 PSIAs in 75 countries and 14 sectors. Total Bank and other donor support to PSIAs over FY04-06 was $15 million. Development literature has emphasized the importance of understanding the institutional and political constraints to development, building domestic ownership of policy reforms, and assessing the distributional impacts of policy actions. The PSIA approach has correctly emphasized these aspects. The Bank has produced a substantial body of guidance on how to address these aspects, and that guidance has been refined over time to incorporate lessons learned. Development literature has emphasized the importance of understanding the institutional and political constraints to development, building domestic ownership of policy reforms, and assessing the distributional impacts of policy actions. The PSIA approach has correctly emphasized these aspects. The Bank has produced a substantial body of guidance on how to address these aspects, and that guidance has been refined over time to incorporate lessons learned.